Growth, yield and antioxidant activity of grey oyster mushroom (Pleurotus pulmonarius) grown in sawdust substrate with the supplementation of alkaline materials - M. P. M.F., Radzi; M., Azizah; T., Maininah; A., Sumaiyah (Pakistan Agricultural Scientists Forum, 2021)
The study aims to evaluate the effect of different alkaline materials’ supplementations on grey oyster mushroom (Pleurotus pulmonarius) to assess mycelial growth, initiation of primordial, yield and antioxidant activity. The sawdust substrate for mushroom cultivation was subjected to three different treatments, including lime, zeolite and gypsum, each designed in a completely randomised block with 10 replications. The prescribing of these alkaline materials significantly influences mushroom cultivation. The combinations of gypsum showed the lowest number of days taken for mycelial growth (30.7 ± 4.12 days) and the emergence of primordia (7.7 ± 4.55 days). The mushroom fruiting body collected from each flush showed that zeolite treatment produced the most acceptable yield (62.36 ± 9.67 g) compared to the other treatments. A maximum inhibitory effect against 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radicals, expressed as IC50 value, was emanated by zeolite treatment from the third flush (63.48 ± 28.804 µg/ml). The total phenolic content (TPC) showed that zeolite exerted the highest phenolics in the fourth flush (98.96 ± 10.07 µg GAE/mg). The application of zeolite and gypsum as additives in mushroom breeding is highly recommended for the rapid growth, increase in yield and antioxidant properties of grey oyster mushroom.